Estudio prospectivo de casos de leishmaniasis cutánea en soldados acantonados en Montería (2016)
The objective of this study was to to establish clinics and epidemiologic features of cutaneous leishmaniasis and the treatment response in soldiers of the Tenth Brigade of the army in Monteria. A prospective study of cases sinc October from the 2001 to October of the 2002, was carry out, in which clinical compatible histories of leshmaniasis were analyzed in the Tenth First Brigade. 67 consecutive soldiers whom had been clinically diagnostic of leishmaniasis by the physician were included, all of them gave their consent to participate in the study. Through out a survey applied to each patient enrolled, clinical and epidemiologic data were obtained. Furthermore, from the clinical histories were obtained the information about: number and place of wounds, treatment response, following, control and prevention measures. A frecuency of cases of leishmaniasis cutaneous of the 2,3% was found. The study showed that some zone of the department of Cordoba are endemic for cutaneous leishmaniasis ehich can represent high risk for the military personnel to acquire the illness. The work besides showed that it is necessary to implement preventive measured, and strictly supervision of the chemotherpy received by the soldiers.